(untitled) (Malaysian Management Journal, 2008)
By 2031, it will be a century since the Great Depression, touted as the most dreadful depression in the history of U.S. and the rest of the world, had taken place. In the final decades of last century and in the early years of this century, numerous financial crises and economic depressions, not as severe as the Depression, have occurred, particularly but not limited to, developing countries. Looking at the Depression and today’s arrangements, will a major global depression be looming? This paper begins with a refresher on the events of the Depression, which is followed by the Friedman and Schwartz hypothesis, criticisms against it, other contributing factors to the Depression, a reconciliation of the theories and finally ends with an assessment of the possibility of a return of the Depression in the 21st century based on today’s economic, financial, political, social, and technological considerations.